The Hog1 MAP Kinase Promotes the Recovery from Cell Cycle Arrest Induced by Hydrogen Peroxide in Candida albicans - Correia, Inês; Alonso-Monge, Rebeca; Pla, Jesús (Frontiers in Microbiology, 2017)
Eukaryotic cell cycle progression in response to environmental conditions is controlled via specific checkpoints. Signal transduction pathways mediated by MAPKs play a crucial role in sensing stress. For example, the canonical MAPKs Mkc1 (of the cell wall integrity pathway), and Hog1 (of the HOG pathway), are activated upon oxidative stress. In this work, we have analyzed the effect of oxidative stress induced by hydrogen peroxide on cell cycle progression in Candida albicans. Hydrogen peroxide was shown to induce a transient arrest at the G1 phase of the cell cycle. Specifically, a G1 arrest was observed, although phosphorylation of Mkc1 and Hog1 MAPKs can take place at all stages of the cell cycle. Interestingly, hog1 (but not mkc1) mutants required a longer time compared to wild type cells to resume growth after hydrogen peroxide challenge. Using GFP-labeled cells and mixed cultures of wild type and hog1 cells we were able to show that hog1 mutants progress faster through the cell cycle under standard growth conditions in the absence of stress (YPD at 37°C). Consequently, hog1 mutants exhibited a smaller cell size. The altered cell cycle progression correlates with altered expression of the G1 cyclins Cln3 and Pcl2 in hog1 cells compared to the wild type strain. In addition, Hgc1 (a hypha-specific G1 cyclin) as well as Cln3 displayed a different kinetics of expression in the presence of hydrogen peroxide in hog1 mutants. Collectively, these results indicate that Hog1 regulates the expression of G1 cyclins not only in response to oxidative stress, but also under standard growth conditions. Hydrogen peroxide treated cells did not show fluctuations in the mRNA levels for SOL1, which are observed in untreated cells during cell cycle progression. In addition, treatment with hydrogen peroxide prevented degradation of Sol1, an effect which was enhanced in hog1 mutants. Therefore, in C. albicans, the MAPK Hog1 mediates cell cycle progression in response to oxidative stress, and further participates in the cell size checkpoint during vegetative growth.